Nanostructuring‐Promoted Non‐Equilibrium Phase Transformation of Bi Anodes Toward Diffusion‐Controlled Reaction for K‐Ion Batteries. Issue 48 (31st October 2022) - Zhang, Jing; Kim, Gilseob; Park, Mihui; Zhang, Jiliang; Lee, Suwon; Cui, Yingxue; Zhang, Kai; Zou, Feng; Kang, Yong‐Mook
Abstract: Nanostructuring is regarded as a significant method for improving the reversibility of alloying anodes for potassium‐ion batteries (PIBs). However, it is still unclear how nanostructuring suppresses the mechanical deterioration upon potassiation/depotassiation. In this study, by in situ X‐ray diffraction, a size‐dependent phase transformation mechanism in a nano‐Bi material (≈15 nm), which avoids the voltage plateau mutation of bulk‐Bi material (≈250 nm) caused by an incomplete and irreversible two‐phase reaction is revealed. The potassiation of nano‐Bi follows a stepwise solid‐solution pathway without any phase transitions under nonequilibrium conditions, circumventing the nucleation of a new phase. The distinctive transition pathway, dominated by the diffusion‐controlled reaction, is accompanied by fast ionic transport kinetics and homogeneous diffusion. As a result, particle fracture is inhibited by isotropic expansion stress, developing a route for stable potassium storage. By contrast, the two‐phase transformation of bulk‐Bi is governed by an interface‐controlled reaction under equilibrium conditions with slow and heterogeneous diffusion, leading to a rapid capacity decay from anisotropic expansion. The comparison between equilibrium thermodynamic‐ and non‐equilibrium kinetic‐phase transformations uncovers the intrinsic mechanism explanatory of the mechanical robustness of the size‐reduced alloying anodes, and also emphasizes that solid‐state diffusion must be improved to attain highly fast kinetics with PIBs. Abstract : A comprehensive investigation of the size‐dependent potassiation thermodynamics and kinetics of alloying anodes remains very challenging. Here, it has been revealed that the potassiation of Bi changes from interface‐controlled reaction to diffusion‐controlled reaction through nanostructuring, which suppresses the voltage plateau mutation in the bulk‐Bi. The nanostructured Bi undergoes a nonequilibrium solid‐solution phase transformation, thus particle fracture is inhibited by isotropic expansion stress.